2019
DOI: 10.1061/(asce)gt.1943-5606.0002115
|View full text |Cite
|
Sign up to set email alerts
|

Total Stress Analysis of Soft Clay Ground Response in Centrifuge Models

Abstract: This paper presents one-dimensional ground response simulations of centrifuge models involving soft clay deposits subjected to ground motions of varying intensity. Total stress ground response simulations were performed using equivalent-linear (EL) and nonlinear (NL) methods. Shear strains higher than 10% were mobilized during large ground motions, therefore undrained shear strength of the clay is an important parameter for the simulations. Testing shows that the Bay Mud materials used in centrifuge modeling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The influence of local scour on the free-field soil properties is considered to be negligible (Meymand, 1998;Shang et al, 2016). The nonlinear SRA employs the general quadratic/hyperbolic (GQ/H) model (Groholski et al, 2016) with the shear strength and damping controls (Afacan et al, 2019;Yee et al, 2013). The GQ/H model uses the reference modulus reduction and damping curves proposed by Darendeli…”
Section: Site Response Analysis Considering Scour Effectsmentioning
confidence: 99%
“…The influence of local scour on the free-field soil properties is considered to be negligible (Meymand, 1998;Shang et al, 2016). The nonlinear SRA employs the general quadratic/hyperbolic (GQ/H) model (Groholski et al, 2016) with the shear strength and damping controls (Afacan et al, 2019;Yee et al, 2013). The GQ/H model uses the reference modulus reduction and damping curves proposed by Darendeli…”
Section: Site Response Analysis Considering Scour Effectsmentioning
confidence: 99%
“…In order to provide a shear strength corrected modulus reduction curve, Afacan et al (2014b) modified the modulus reduction curves obtained through the empirical relationships introduced by Darendeli (2001) to match a target shear strength using the procedure from Yee et al (2013).…”
Section: Centrifuge Modelsmentioning
confidence: 99%
“…The curves were further modified to match a target rate-adjusted shear strength, and Afacan et al (2014b) showed that the use of strain-rate-adjusted profiles of undrained shear strength allows to obtain more accurate predictions in ground response analysis. The centrifuge model was shaken with 19 earthquake ground motions with peak accelerations varying from 0.02g to 0.6g.…”
Section: Centrifuge Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this study utilizes an improved modeling of site response at large strains by adjusting the backbone curves and incorporates epistemic uncertainties in soil parameters considering NL constitutive modeling. Note that prior researchers, such as Yee et al (2013) and Afacan et al (2019), have demonstrated the importance of shear strength in the modeling of site response at large strains and that researchers, such as Yee et al (2013) and Groholski et al (2016), have provided methods to adjust the backbone curve to account for it. Finally, another key aspect of this work is to quantify site response uncertainty using both the actual recordings at a geotechnical downhole array (Yazdi et al, 2022; Yee et al, 2013; Zogh et al, 2021) and the predicted median response spectra for different levels of intensity to assess the reliability of using the predicted median response spectra in case the actual recordings at the location of site are not available.…”
Section: Introductionmentioning
confidence: 99%